## 1995 Assignment: Student Solutions

### From Mandy Lutz:

```1 + 9 - 9 + 5 = 6
-1 + 9 - 9 + 5 = 4
-1 + 9 + 9 - 5 = 12
1 + sqrt9 + 9 - 5 = 8
-1 - sqrt9 + 9 + 5 = 10
1 - sqrt9  + 9 - 5 = 2
1*(9 + 9 - 5) = 13
1*(9 - 9 + 5) = 5
1 + sqrt(sqrt9*sqrt9) + 5 = 9
1(9 - sqrt9 - 5) = 1
1 + 9/9 + 5 = 7
19 - sqrt9 - 5 = 11
1 + 9 + 9 - 5 = 14
-1 + (sqrt9*sqrt9) - 5 = 3
```

### From Megan McClenaghan:

```1 - 9 + sqrt(9) + 5 = 0
1(9 - sqrt(9) - 5) = 1
1 + sqrt(9) + sqrt(9) - 5 = 2
-1 + 9 - 5 = 3
-1 - 9 + 9 + 5 = 4
19 - 9 - 5 = 5
1 + 9 - 9 + 5 = 6
1*sqrt(9) + 9 - 5 = 7
1 + sqrt(9) + 9 - 5 = 8
1^9 + sqrt(9) + 5 = 9
-1 + sqrt(9) + sqrt(9) + 5 = 10
19 - sqrt(9) - 5 = 11
1 + sqrt(9) + sqrt(9) + 5 = 12
1*9 + 9 - 5 = 13
1*sqrt(9)*sqrt(9) + 5 = 14
19 - 9 + 5 = 15
```

### From Sara Rangooni:

```1. 1* square root 9 + square root 9 - 5 = 1

2. 1+ square root nine + square root 9 - 5 = 2

3. -1 + square root 9 * square root 9 - 5 = 3

4. 1 * -9 divided by 9 + 5 = 4

5. 1*9 - 9 + 5 = 5

6. 1 + 9 - 9 + 5 = 6

7. 1 + (9 divided by 9 + 5) = 7

8. 1+ square root 9 + 9 - 5 = 8

9. 1 to the power of 9 + square root 9 + 5 = 9

10. -1 + square root 9 + square root 9 + 5 = 10

11. 19 - square root 9 - 5 = 11

12. 1 + square root 9 + square root 9 + 5 = 12

13. 1 * 9 + 9 - 5 = 13

14. 1 + 9 + 9 - 5 = 14

15. 19 - 9 + 5 = 15
```

### From Shalini Sookar:

```-1*sqrt(9) + 9 - 5 = 1

1 + sqrt(9) + sqrt(9) - 5 = 2

-1^9 + 9 - 5 = 3

-1 + 9 - 9 + 5 = 4

1 + sqrt(9*9) - 5 = 5

1 - 9 + 9 + 5 = 6

1*sqrt(9) + 9 - 5 = 7

1 + 9 + sqrt(9) - 5 = 8

1^9 + sqrt(9) + 5 = 9

-1 - sqrt(9) + 9 + 5 = 10

1*sqrt(9) + sqrt(9) + 5 = 11

1 + sqrt(9) + sqrt(9) + 5 = 12

1*9 + 9 - 5 = 13

1 + 9 + 9 - 5 = 14

19 - 9 + 5 = 15
```